Growth regulation by heparin in the vascular wall - Karnovsky, Morris, John (My University, 1983)
Vascular smooth muscle proliferation follows upon endothelial injury, and is thought to be an early component in the pathogenesis of atherosclerosis, and a possible noxious consequence of vascular surgery. We have shown that heparin suppresses vascular smooth muscle proliferation iri vivo and in vitro. The inhibitory effect is specific for heparin, and not other anions, and is not related to the antithrombin III binding activity of heparin. It is dependent on the size of the molecule, (hexasaccharidees or smaller being ineffective), and O-sulfation, but not N-sulfation
A Thesis Submitted to the Faculty of Medicine University of the Witwatersrand, Johannesburg in fulfillment of the requirements for the Degree of Doctor of Science in Medicine Boston, U.S.A. 1983
Keywords: Heparin; In Vitro Techniques; Muscle, Smooth, Vascular